2011
DOI: 10.1038/leu.2011.73
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic differentiation of umbilical cord blood-derived very small embryonic/epiblast-like stem cells

Abstract: A population of CD133+lin−CD45− very small embryonic-like stem cells (VSELs) has been purified by multiparameter sorting from umbilical cord blood (UCB). In order to speed up isolation of these cells, we employed anti-CD133-conjugated paramagnetic beads followed by staining with Aldefluor to detect aldehyde dehydrogenase (ALDH) activity; we subsequently sorted CD45−/GlyA−/CD133+/ALDHhigh and CD45−/GlyA−/CD133+/ALDHlow cells, which are enriched for VSELs, and CD45+/GlyA−/CD133+/ALDHhigh and CD45+/GlyA−/CD133+/A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
76
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(79 citation statements)
references
References 23 publications
3
76
0
Order By: Relevance
“…VSELs-derived HSCs harvested from these co-cultures reconstitute murine bone marrow after total body irradiation [43]. The Umbilical Cord Blood (UCB)-purified VSELs have also been reported to differentiate into neural cells [44] and after co-culture over OP-9 stroma cells were specified into HSCs similar to murine BM-derived VSELs [45]. Apart from umbilical cord blood and bone marrow, VSELs have also been reported in Wharton's jelly and gonadal tissue [46][47][48][49][50][51].…”
Section: Developmental Origin Of Vselsmentioning
confidence: 99%
“…VSELs-derived HSCs harvested from these co-cultures reconstitute murine bone marrow after total body irradiation [43]. The Umbilical Cord Blood (UCB)-purified VSELs have also been reported to differentiate into neural cells [44] and after co-culture over OP-9 stroma cells were specified into HSCs similar to murine BM-derived VSELs [45]. Apart from umbilical cord blood and bone marrow, VSELs have also been reported in Wharton's jelly and gonadal tissue [46][47][48][49][50][51].…”
Section: Developmental Origin Of Vselsmentioning
confidence: 99%
“…VSELs were also identified in neonatal retina and involved in optic nerve retinal regeneration in a rodent model [34]. VSELs may also play a major role as populations of cells that preferentially give rise to induced pluripotent stem cells (iPSCs) when BM-derived stromal cells are induced to pluripotency by genetic manipulation [35].In particular, VSELs derived by parthenogenesis have also been identified successfully [36].…”
Section: Molecular Biology and Functional Features Of Vselsmentioning
confidence: 99%
“…Further study demonstrated that VSELs can not primarily reveal hematopoietic ability immediately from isolation and expansion, but may eventually acquire hematopoietic potential following co-culture in hematopoiesis permissive environment over OP9 stroma feeder layer and reconstitute hematopoiesis in lethally irradiated mice 4-6 weeks after transplantation [26].…”
Section: Molecular Biology and Functional Features Of Vselsmentioning
confidence: 99%
“…VSELs fulfill the above-listed in vitro criteria, despite the fact that they are highly quiescent in culture, and special conditions are needed to differentiate them into various lineages [61,62,[74][75][76][77][78][79][80]. However, VSELs do not fulfill the in vivo criteria, as they do not complete blastocyst development and do not grow teratomas [25,81].…”
Section: Question 3 -The Role Of Parentally Imprinted Genes In Maintamentioning
confidence: 99%